Preterm labor is characterized by a high abundance of amniotic fluid prostaglandins in patients with intra-amniotic infection or sterile intra-amniotic inflammation. (17th December 2021) - Peiris, Hassendrini N.; Romero, Roberto; Vaswani, Kanchan; Reed, Sarah; Gomez-Lopez, Nardhy; Tarca, Adi L.; Gudicha, Dereje W.; Erez, Offer; Maymon, Eli; Mitchell, Murray D.
Abstract: Objective: To distinguish between prostaglandin and prostamide concentrations in the amniotic fluid of women who had an episode of preterm labor with intact membranes through the utilisation of liquid chromatography-tandem mass spectrometry. Study design: Liquid chromatography-tandem mass spectrometry analysis of amniotic fluid of women with preterm labor and (1) subsequent delivery at term (2) preterm delivery without intra-amniotic inflammation; (3) preterm delivery with sterile intra-amniotic inflammation (interleukin (IL)-6>2.6 ng/mL without detectable microorganisms); and (4) preterm delivery with intra-amniotic infection [IL-6>2.6 ng/mL with detectable microorganisms]. Results: (1) amniotic fluid concentrations of PGE2, PGF2α, and PGFM were higher in patients with intra-amniotic infection than in those without intra-amniotic inflammation; (2) PGE2 and PGF2α concentrations were also greater in patients with intra-amniotic infection than in those with sterile intra-amniotic inflammation; (3) patients with sterile intra-amniotic inflammation had higher amniotic fluid concentrations of PGE2 and PGFM than those without intra-amniotic inflammation who delivered at term; (4) PGFM concentrations were also greater in women with sterile intra-amniotic inflammation than in those without intra-amniotic inflammation who delivered preterm; (5) amniotic fluid concentrations of prostamides (PGE2 -EA and PGF2α -EA) were not different among patients with preterm labor; (6) amniotic fluid concentrations of prostaglandins, but no prostamides, were higher in cases with intra-amniotic inflammation; and (7) the PGE2 :PGE2 -EA and PGF2α :PGF2α -EA ratios were higher in patients with intra-amniotic infection compared to those without inflammation. Conclusions: Mass spectrometric analysis of amniotic fluid indicated that amniotic fluid concentrations of prostaglandins, but no prostamides, were higher in women with preterm labor and intra-amniotic infection than in other patients with an episode of preterm labor. Yet, women with intra-amniotic infection had greater amniotic fluid concentrations of PGE2 and PGF2α than those with sterile intra-amniotic inflammation, suggesting that these two clinical conditions may be differentiated by using mass spectrometric analysis of amniotic fluid.